Příběh apendixu - Lukáš, Karel (Casopis lekaru ceskych, 2015)
Acute appendicitis is the most frequent acute abdominal emergency. Appendicitis may have been recorded by Aretaeus the Cappadocean in 30 AD. A description of the appendix was provided by the anatomist Berengario de Carpi in 1521. The first appendicectomy was performed by Claudius Amyand in 1735. Turning point in the story of appendix was public lecture of pathologist-physician Reginald Fitz in 1886. Fitz used the term "appendicitis". The area of maximal tenderness with appendicitis was immortalised by Charles McBurney. In the story of appendicitis many names figure, for example Niels Thorkild Rovsing, Jacob Moritz Blumberg, Otto Lanz, Frederic Treves and other. Kurt Semm introduced laparoscopic appendicectomy in 1988.
Keywords: History, 17th Century; History, 20th Century; dějiny 16. století; Humans; dějiny 17. století; History, 16th Century; lidé; Appendicitis; appendix - appendicitis.; History, 19th Century; Acute Disease; apendix; dějiny 18. století; akutní nemoc; Appendix; dějiny 20. století; History, 18th Century; dějiny 19. století; apendektomie; Appendectomy; apendicitida